2021
DOI: 10.1007/s11356-021-12709-z
|View full text |Cite
|
Sign up to set email alerts
|

Significance between air pollutants, meteorological factors, and COVID-19 infections: probable evidences in India

Abstract: Graphical abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease represents the causative agent with a potentially fatal risk which is having great global human health concern. Earlier studies suggested that air pollutants and meteorological factors were considered as the risk factors for acute respiratory infection, which carries harmful pathogens and affects the immunity. The study intended to explore the correlation between air pollutants, meteorological factors, and the da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 157 publications
1
19
0
Order By: Relevance
“…First, 1995 duplicates were excluded and then 3131 and 70 records were excluded based on the title and abstract, respectively. Full texts of 132 records were evaluated and in the end 35 articles that met the criteria were included in the study ( Adhikari and Yin, 2020 ; Azuma et al, 2020 ; Berg et al, 2021 ; Cabrera-Cano et al, 2021 ; Coker et al, 2020 ; Dales et al, 2021 ; De Angelis et al, 2021 ; Elliott et al, 2021 ; Fang et al, 2021 ; Hoang and Tran, 2020 ; Hoang et al, 2020 ; Huang and Brown, 2021 ; Jiang et al, 2020 ; Konstantinoudis et al, 2021 ; Linares et al, 2021 ; Lorenzo et al, 2021 ; Lu et al, 2021 ; Ma et al, 2021 ; Qeadan et al, 2021 ; Petroni et al, 2020 ; Rodriguez-Villamizar et al, 2020 ; Sahoo, 2021 ; Sanchez-Piedra et al, 2021 ; Setti et al, 2020 ; Stieb et al, 2020 ; Travaglio et al, 2021 ; Valdés Salgado et al, 2021 ; Wang et al, 2020 ; Wu et al, 2020a , 2020b , 2020b ; Xu et al, 2020 ; Zhang et al, 2021 ; Zheng et al, 2021 ; Zhou et al, 2021 ; Zhu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, 1995 duplicates were excluded and then 3131 and 70 records were excluded based on the title and abstract, respectively. Full texts of 132 records were evaluated and in the end 35 articles that met the criteria were included in the study ( Adhikari and Yin, 2020 ; Azuma et al, 2020 ; Berg et al, 2021 ; Cabrera-Cano et al, 2021 ; Coker et al, 2020 ; Dales et al, 2021 ; De Angelis et al, 2021 ; Elliott et al, 2021 ; Fang et al, 2021 ; Hoang and Tran, 2020 ; Hoang et al, 2020 ; Huang and Brown, 2021 ; Jiang et al, 2020 ; Konstantinoudis et al, 2021 ; Linares et al, 2021 ; Lorenzo et al, 2021 ; Lu et al, 2021 ; Ma et al, 2021 ; Qeadan et al, 2021 ; Petroni et al, 2020 ; Rodriguez-Villamizar et al, 2020 ; Sahoo, 2021 ; Sanchez-Piedra et al, 2021 ; Setti et al, 2020 ; Stieb et al, 2020 ; Travaglio et al, 2021 ; Valdés Salgado et al, 2021 ; Wang et al, 2020 ; Wu et al, 2020a , 2020b , 2020b ; Xu et al, 2020 ; Zhang et al, 2021 ; Zheng et al, 2021 ; Zhou et al, 2021 ; Zhu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond three air pollutants: NO 2 , PM 2.5 and O 3 that were investigated in this study, other air pollutants including carbon monoxide (CO), particulate matter with a diameter less than 10 μm or less (PM 10 ), and sulfur dioxide (SO 2 ) are also important ambient air pollutants that have been investigated for their associations with COVID-19 prevalence and incidence, mostly in Europe and China. Several studies have found associations between exposure to PM 10 and increased number of COVID-19 cases ( Setti et al, 2020 ; Bianconi et al, 2020 ; De Angelis et al, 2021 ; Jiang et al, 2020 ; Zhu et al, 2020b ; Solimini et al, 2021 ; Sahoo, 2021 ; Zheng et al, 2021 ; Ma et al, 2021 ; Saez et al, 2020 ), while fewer studies have investigated the role of CO and SO 2 for their associations with COVID-19 incidence and transmissibility and results were inconsistent across studies ( Meo et al, 2021 ; Ran et al, 2020 ). The associations of short- and long-term exposures to PM 10 , SO 2 and CO in Southern California need to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in Turkmenistan, where initially the presence of COVID-19 cases was not recognized, reductions in NO 2 levels were the lowest. However, it is possible that a small part of the reduction may also be caused by meteorological variability (wind, temperature, cloud cover, and humidity), which can affect the transport and lifespan of NO x (Bassani et al 2021 ; Sahoo 2021 ).…”
Section: Resultsmentioning
confidence: 99%